Pertanggungjawaban Notaris dan Akibat Hukum Pengesahan Pendirian Perseroan Terbatas Melalui Sistem Administrasi Badan Hukum - Tia Sanitra Gumilang (Lex Renaissance, 2019)
This study aims to examine the accountability of a notary in the process of establishing a Limited Liability Company (PT) through the Legal Entity Administration System (SABH) and the legal consequences if the notary innovates in the process of establishing a PT through a Legal Entity Administration System (SABH). This research is normative juridical, using a statutory approach, collecting data with literature and document studies. The results of this study conclude that the responsibility of a notary in the process of establishing a PT is not just an accountability for the deed he made, but the notary is also fully responsible for any mistakes made in the process of establishing PT. The notary’s liability is stated in the electronic statement that the notary is fully responsible for what is filled in and uploaded in accordance with statutory regulations. Therefore, the principle of notarial prudence is needed so that the mistakes made by the notary do not affect the parties and third parties related to the deed. The legal consequences if a notary innovates a law that is contrary to the laws and regulations is that the notarial deed can be declared null and void by law, so that it can have an impact on the parties and third parties related to the said legal act. Legal innovations by notaries are allowed as long as they are still in the corridor of the notary's obligations. Innovation through legal discovery is used so that the application of the rule of law to an event can be done precisely and relevant.